Pelatihan Pengamatan Kupu-Kupu Menggunakan Aplikasi Odolepi Berbasis Android di SMA Muhammadiyah Pamijahan Bogor - Murwitaningsih, S.; Ermawati, IR.; Arjun, Arjun; Nanda, N. (Jurnal Indonesia Mengabdi, 2020)
This community partnership program is aimed at downstream activities and mentoring training programs for observing the diversity of butterflies and dragonflies at SMA Muhammadiyah Pamijahan, Bogor, West Java. In addition, based on observations from previous research, information about the diversity of dragonflies and butterflies in the Cibodas Botanical Gardens was also produced, a guidebook for observing dragonflies and butterflies in printed and mobile form, named Odolepi. This application can be displayed on android-based mobile phones. Meanwhile, the target in this Service at SMA Muhammadiyah Pamijahan Bogor is an innovation activity that is given in the form of insect observation activities according to the subject matter in biology subjects, namely butterflies by using observation guidelines in the form of mobile or android which can be stored in mobile phones. so it can be used anytime and anywhere. For students who do not have an android mobile phone, the service team will provide a manual in printed form. As for the results of display conformity getting 77.54%, language suitability of 81.87 5 and media suitability of 76.27% it can be concluded that the media used it's been very good. This activity is expected to increase knowledge, skills and of course attitudes to better protect and preserve butterflies which in turn preserves the environment.